Identification and Definition of Early Aspects - A Prototype of Method - Resende, Antônio Maria Pereira de; da Cunha, Adilson Marques; Costa, Heitor Augustus Xavier (INFOCOMP Journal of Computer Science, 2010)
This paper briefly presents the conceptual model of the Method for Early Aspect (EA) Identification and Definition (MEAID). It also details activities named Early Aspects Candidates Identification with a set of heuristics and Early Aspects Definition with decision equation. The MEAID has being developed to support software engineering professionals reduce empirical and subjective decisions, aiming to increase efficacy and efficiency on such activity. Results from a scientific experimentation, based on Experimental Software Engineering concepts and their statistical analysis applying Student’s T Test statistical method are presented as well.